2010
DOI: 10.1007/s11695-010-0341-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of a Prospective Study on Laparoscopic Adjustable Gastric Banding for Morbid Obesity

Abstract: After LAGB, band removal was necessary for complications or insufficient weight loss in 24% of patients. Nearly half of the patients achieved a more than 50% EWL, but in 88%, a more than 10% EWL was observed. LAGB can achieve an acceptable weight loss in some patients, but the failure in one out of four patients does not allow proposing it as a first-line option for the treatment of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Revisional bariatric surgery comprises 5%-15% of total cases of bariatric surgery [3,4,5]. The rate of revisional surgery is 20%-60% after LAGB [6,7,8,9,10,11], 9%-17% after RYGB [6,10,12,13], and 9%-11% after SG [14,15]. Although many articles have investigated the results of various bariatric procedures used as the initial surgical intervention for morbid obesity, studies addressing the proper revisional surgery of choice after failed primary surgery remain limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Revisional bariatric surgery comprises 5%-15% of total cases of bariatric surgery [3,4,5]. The rate of revisional surgery is 20%-60% after LAGB [6,7,8,9,10,11], 9%-17% after RYGB [6,10,12,13], and 9%-11% after SG [14,15]. Although many articles have investigated the results of various bariatric procedures used as the initial surgical intervention for morbid obesity, studies addressing the proper revisional surgery of choice after failed primary surgery remain limited.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators prefer to perform the operations in two steps for several reasons, including a predictable surgical time, lower risk of postoperative complications, and reduced incidence of delayed anastomotic stricture [8,17,27]. Others have advocated single-staged operation, suggesting that it could be safely performed without increasing the risk of surgical complications [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Himpens et al 21 also found 61.0% complication and 59.8% reoperation rate after 12-year follow-up. During 11-year follow-up, Van Nieuwenhove et al 22 reported that 50% of patients had complications. A systematic review conducted by Tice et al 23 has indicated that LAGB had higher reoperation rate compared with RYGBP.…”
Section: Commentsmentioning
confidence: 99%
“…Adverse event rates and reoperation rates were generally poorly reported. One study on more than 700 patients reports a reoperation rate of 23% after LAGB at 7 years of follow up [9]. Overall, the long term weight loss after bariatric surgery is greater than 60% and stabilization is seen 2 years after surgery [10].…”
Section: Literaturementioning
confidence: 99%